PENGEMBANGAN KONTEN INTERAKTIF MATA KULIAH PRESERVASI PANGAN BERBASIS PROJECT BASED E-LEARNING PADA PRODI PENDIDIKAN VOKASIONAL SENI KULINER DI UNIVERSITAS PENDIDIKAN GANESHA - Ni Putu Serly Widyaningsih; I Gede Bendesa Subawa; Dessy Seri Wahyuni (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2022)
This study aims to generate and implement and describe user experiences that involve educators and students in development of interactive learning content for food preservation courses based on project based e-learning in Vocasional Education Program of Culinary Arts at Ganesha Education University, This research is a type of Development Research and uses the ADDIE model, The subjects in this study were 4th semester students of the Culinary Arts Vocational Education study program and one lecturer in charge of the Food Preservation course, based on the stages that have been passed to produce interactive content in food preservation courses using adobe captivate based on project based learning, with the acquisition of the coefficient of content experts and media experts of 1.00 with the criteria of "Very Valid", then in individual trials, the percentage is 91.55% with "Very Good" qualifications, small group trials get a percentage of 91.2% with "Very Good" qualifications, then in the field trials, 90.7% with qualifications " Very Good", The results of the effectiveness test with the N-gain calculation obtained a value of 0.80 with the criteria of Effective, In addition, the results of the user experience test on the attractiveness, perspicuity, dependability, stimulation and novelty aspects obtained the "Excellent" category and the efficiency aspect obtained the "Good" category. Keywords: Project-Based Learning, Interactive Content, Food Preservation